1978
DOI: 10.1099/00221287-106-2-277
|View full text |Cite
|
Sign up to set email alerts
|

The Requirement of Oxygen for the Utilization of Maltose, Cellobiose and D-Galactose by Certain Anaerobically Fermenting Yeasts (Kluyver Effect)

Abstract: Of the yeasts that ferment D-glucose anaerobically, over 4076 can use certain glycosides and D-galactose oxidatively, but cannot ferment them. This phenomenon is here called the Kluyver effect. More than half the yeast species described which exhibit this effect do so with more than one substrate. Yeasts showing the effect with maltose, cellobiose and D-galactose were compared with fermenting strains, to determine whether enzyme inactivation or cessation of sugar uptake was responsible. The different responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

1983
1983
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 16 publications
1
46
0
1
Order By: Relevance
“…Along with its observed role in the short-term Crabtree effect (van Urk et al, 1989), this enzyme can be considered an important switchpoint in mediating the various 0, effects observed in yeasts. Weusthuis et al (1994) indicated that there were three possible reasons why the Kluyver effect could be caused by differences in monosaccharide and disaccharide metabolism, sugar transport, disaccharide hydrolysis, and sugar-specific regulatory mechanisms which occur before the level of pyruvate (reiterating the conclusions of Sims and Barnett, 1978). The explanation proposed by Weusthuis eta!, was that there might be a mechanism that tunes disaccharide uptake and hydrolysis in response to 0, concentration or redox potential.…”
Section: Oxygen and Yeast Metabolismmentioning
confidence: 78%
See 2 more Smart Citations
“…Along with its observed role in the short-term Crabtree effect (van Urk et al, 1989), this enzyme can be considered an important switchpoint in mediating the various 0, effects observed in yeasts. Weusthuis et al (1994) indicated that there were three possible reasons why the Kluyver effect could be caused by differences in monosaccharide and disaccharide metabolism, sugar transport, disaccharide hydrolysis, and sugar-specific regulatory mechanisms which occur before the level of pyruvate (reiterating the conclusions of Sims and Barnett, 1978). The explanation proposed by Weusthuis eta!, was that there might be a mechanism that tunes disaccharide uptake and hydrolysis in response to 0, concentration or redox potential.…”
Section: Oxygen and Yeast Metabolismmentioning
confidence: 78%
“…Accordingly, this definition suggests that the Kluyver effect is not dependent on the 02 concentration, but reflects an inability to metabolize the disaccharide fermentatively. Sims and Barnett (1978) concluded that the Kluyver effect resulted from the requirement for 0,by sugar transport. In later work (Sims and Barnett, 1981), these authors showed that pyruvate decarboxylase activities were reduced when grown on the disaccharide.…”
Section: Oxygen and Yeast Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In some yeasts, certain 351 sugars (often disaccharides) which support vigorous oxidative growth, cannot be fermented. In the literature, this effect has been termed the Kluyver effect (Sims & Barnett 1978). We have studied this poorly understood phenomenon with respect to the utilization of maltose by the facultatively fermentative, Crabtree-negative yeast Candida utilis.…”
Section: Effects Of Oxygen On Growth Kineticsmentioning
confidence: 99%
“…High dosages of both the permease and maltase genes were indeed necessary for K. lactis cells to grow on maltose in the absence of respiration. These results strongly suggest that the sugar uptake step is the major bottleneck in the fermentative assimilation of certain sugars in K. lactis and probably in many other yeasts.Kluyveromyces lactis and many other yeast species can grow on galactose and certain oligosaccharides (such as raffinose and maltose) aerobically, but they cannot grow on these sugars anaerobically or in the absence of respiration (15,18,19,35). Assimilation of these carbon sources occurs only under respiring conditions.…”
mentioning
confidence: 99%